As fachadas azulejares sergipanas : simbologia, memória e história - Paulo, Karoline Padilha de (2023)
The present work has the objective to understand façade tiles as a cultural heritage and symbolic object of the past social dynamics of Sergipe, delimiting, as a study cut, its territory from the end of the 19th to the beginning of the 20th century, the interval in which the practice occurred in the region. Such proposed perspectives are possible by recognizing the historical fragments delegated as a crucial tool for exercising a community's memory, integrating with different layers of its socio-spatial context of insertion, and understanding its materiality, function, and possibly attributed symbolisms. However, there are few records and studies about this Sergipe heritage, which, added to the lack of public and private initiatives aimed at its maintenance and preservation, points to its possible complete disappearance. Therefore, during the development of the work, we sought not only to understand the trajectory and historical importance of tile art in the 19th century but also to register and entail in the most complex fields of its development in the national territory. Therefore, the objective was to understand first the historical context in which art took shape, exploring the conditions and currents of influences that operated in Sergipe territory and that, in turn, conditioned its tile collection. Then, the technical and artistic specificities of façade tiles in Sergipe were analyzed, to expand the existing knowledge of its collection, which currently comprises a total of fifteen buildings of civil architecture distributed among the municipalities of Laranjeiras, Maruim, Estância, Lagarto, and Simão Dias. Finally, the symbolic issues inherent in both tile art and its use as a collective practice were explored, effectively inserting it into the socio-spatial power dynamics of its time. Therefore, given the nature of the object presented, the study reconciled historical analysis methodologies with those developed in the Conservation and Restoration Technology field, integrating an extensive documentary analysis of written, iconographic, and oral sources. Through the evidentiary methodological premise presented by Ginzburg (1989), the different layers of the national past were explored, from the connection of the information present in texts, laws, and decrees, with the more specific ones apprehended in old periodicals and post-mortem inventories of members of the Sergipe community in the second half of the 19th century. In addition to the collected written sources, an extensive graphic-photographic assortment was used, which ranged from iconographic and iconological analysis of old photographs and illustrations of the studied cities through the methodological premises presented by Kossoy (1941), to the production of maps, boards, illustrative images, and representative schemes of the theoretical discussions developed. Graphics productions complemented by the documentation process of the specimens studied through the elaboration of Identification Sheets (FIDs) following the methodology of analysis and patrimonial documentation developed by Tinoco (2009). Finally, to collect the orality of the local community, interviews of a non-structured nature, announced by Marconi and Lakatos (2003), were conducted to revisit part of the memory of the municipalities. Thus, all objectives and joint actions allowed the recording and continuity of a piece of Sergipe's heritage memory.